Effects of the Nasal Cavity Complexity on the Pharyngeal Airway Fluid Mechanics: A Computational Study. - Aljawad, Hussein; Rüttgers, Mario; Lintermann, Andreas; Schroöder, Wolfgang; Lee, Kyungmin Clara (Journal of Digital Imaging, 2021)
The impact of the human nasal airway complexity on the pharyngeal airway fluid mechanics is investigated at inspiration. It is the aim to find a suitable degree of geometrical reduction that allows for an efficient segmentation of the human airways from cone-beam computed tomography images. The flow physics is simulated by a lattice Boltzmann method on high-performance computers. For two patients, the flow field through the complete upper airway is compared to results obtained from three surface variants with continuously decreasing complexity. The most complex reduced airway model includes the middle and inferior turbinates, while the moderate model only features the inferior turbinates. In the simplest model, a pipe-like artificial structure is attached to the airway. For each model, the averaged pressure is computed at different cross sections. Furthermore, the flow fields are investigated by means of averaged velocity magnitudes, in-plane velocity vectors, and streamlines. By analyzing the averaged pressure loss from the nostrils to each cross section, it is found that only the most complex reduced models are capable of approximating the pressure distribution from the original geometries. In the moderate models, the geometry reductions lead to overpredictions of the pressure loss in the pharynx. Attaching a pipe-like structure leads to a higher deceleration of the incoming flow and underpredicted pressure losses and velocities, especially in the upper part of the pharynx. Dean-like vortices are observed in the moderate and pipe-like models, since their shape comes close to a 90 ∘ -bend elbow pipe.